2017
DOI: 10.3201/eid2301.160239
|View full text |Cite
|
Sign up to set email alerts
|

Dolphin Morbillivirus Associated with a Mass Stranding of Sperm Whales, Italy

Abstract: In September 2014, seven sperm whales were stranded along Italy’s Adriatic coastline. Postmortem investigations on 3 female adult whales and 1 male fetus carried by the largest female revealed molecular and immunohistochemical evidence of dolphin morbillivirus infection. A possible role of the virus in the stranding event was considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 10 publications
0
35
0
Order By: Relevance
“…In contrast to host-specific pathogens belonging to the same genus, such as Measles Virus, RPV and PPRV, the broad and expanding host range of DMV, testified by the present report and by numerous cases of DMV infection reported in the last 5 years in the Mediterranean Sea ( Mazzariol et al, 2013 , 2016 , 2017 ; Centelleghe et al, 2016 ), being additional corroborated by the results of recent sero-epidemiological surveys ( Profeta et al, 2015 ), appears to show a number of similarity with the behavior of CDV, despite the low phylogenetic and genetic homology degree between these two morbilliviruses ( Van Bressem et al, 2014 ). Spill-over events at the end epidemic outbreaks or during endemic infection’s condition, resulting from interactions between CDV-infected dogs and wild carnivore and pinniped species, have led to mass mortalities ( Di Guardo et al, 2005 ; Beineke et al, 2015 ).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In contrast to host-specific pathogens belonging to the same genus, such as Measles Virus, RPV and PPRV, the broad and expanding host range of DMV, testified by the present report and by numerous cases of DMV infection reported in the last 5 years in the Mediterranean Sea ( Mazzariol et al, 2013 , 2016 , 2017 ; Centelleghe et al, 2016 ), being additional corroborated by the results of recent sero-epidemiological surveys ( Profeta et al, 2015 ), appears to show a number of similarity with the behavior of CDV, despite the low phylogenetic and genetic homology degree between these two morbilliviruses ( Van Bressem et al, 2014 ). Spill-over events at the end epidemic outbreaks or during endemic infection’s condition, resulting from interactions between CDV-infected dogs and wild carnivore and pinniped species, have led to mass mortalities ( Di Guardo et al, 2005 ; Beineke et al, 2015 ).…”
Section: Discussionmentioning
confidence: 44%
“…Similarly to wild carnivores for CDV, the species recently reported to be susceptible to morbilliviral infection, such as that herein described, could subsequently act as reservoirs for DMV, thus being a possible source of spillback events involving naive population of classic hosts and supporting the presence and circulation of DMV in the Mediterranean area ( Beineke et al, 2015 ; Mazzariol et al, 2016 , 2017 ).…”
Section: Discussionmentioning
confidence: 58%
“…Similar Th2 immune response was observed in other studies that evaluated the expression of cytokines in different cetacean tissues ( Jaber et al, 2010 ). A variety of infections caused by intracellular pathogens in cetaceans have been reported and may be associated with the mass stranding events of cetaceans ( Cvetnic et al, 2016 ; Domingo et al, 1990 ; Domingo et al, 1992 ; Dubey et al, 2007 ; Dubey et al, 2008 ; Mazzariol et al, 2016 ; Mazzariol et al, 2017 ). In addition, previous studies suggested that Ag contamination exists in all aspects of the marine ecosystem, and cetaceans may have been negatively affected by Ag contamination ( Becker et al, 1995 ; Caceres-Saez et al, 2013 ; Chen et al, 2017 ; Dehn et al, 2006 ; Kunito et al, 2004 ; Li et al, 2018a ; Mendez-Fernandez et al., 2014 ; Reed et al, 2015 ; Rosa et al, 2008 ; Seixas et al, 2009 ; Woshner et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, while a CeMV isolate from the Southern Hemisphere that was identified almost simultaneously in Guyana dolphins (Sotalia guianensis) along the Atlantic coast of Brazil as well as in Indo-Pacific bottlenose dolphins (Tursiops aduncus) from Western Australia [15-17] appears to be the one most closely related to RPV among the 5 hitherto defined CeMV strains [3], it should be once again recalled that fatal cases of infection caused by Dolphin Morbillivirus (DMV, a CeMV strain) have been recently reported in Italy among Eurasian otters, an endangered wild mammal species with a mixed water-terrestrial ecology [7]. Furthermore, starting from 2011, DMV has shown a considerable expansion of its host range in the Western Mediterranean Sea, with lethal episodes of infection having been reported in fin whales as well as among mass-stranded sperm whales [4,5,18], while deadly cases of DMV infection have also been described in a Cuvier's beaked whale (Ziphius cavirostris) individual [19] and, surprisingly, even in a captive harbour seal [6].…”
mentioning
confidence: 99%